Body, Territory and Family in Afro-Colombian Communities Residing in Bogotá - Useche González, Gigson (Rastros Rostros, 2014)
This article is the result of the research study being conducted in the sub-area of research titled “Ethnoeducation: A Space for Rethinking Education in Colombia”, which is linked to the Faculty of Education at the Universidad Libre. It seeks to characterize the ethnic group made up of Afro- Colombian communities who are displaced in the country’s current political, economic and social landscape, and who are hurriedly inserted into the urban social fabric, thus damaging their quality of life and human development, and affecting the urban social dynamics. This situation merits both research and pedagogical intervention in searching for and realizing educational proposals and life plans that contribute to the cultural and social rebuilding of these ethnic communities.